TI_GERICHTE 12.2009.149 vom 18. Juni 2010 , Domanda riconvenzionale - competenza territoriale - mandato - atto illecito (penale) - prescrizione - TI Tribunale d'appello (2010)
Domanda riconvenzionale - competenza territoriale - mandato - atto illecito (penale) - prescrizione